Increasing Children’s Awareness in Adopting Healthy Lifestyles to Prevent the Covid-19 Virus - Prawiyogi, Anggy Giri; Suparman, Tarpan (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
Real Work Lectures (KKN) are community service activities in certain areas or educational institutions. This KKN activity aims to provide real field work experience in the field of forming an independent and responsible attitude in carrying out work in the field. This KKN implementation was carried out online starting from July 1 2021 to July 31 2021 in North Pangulah Village, Kotabaru District. One of the individual work programs carried out by 17 students in North Pangulah Village was socialization regarding "Increasing Children’s Awareness in Adopting a Healthy Lifestyle to Prevent the Covid-19 Virus". The spread of Corona Virus Disease 2019 (Covid-19) has now become a pandemic outbreak in Indonesia. With the emergence of this disease outbreak, it is important to maintain health and the immune system. Therefore, it is important to maintain a clean and healthy lifestyle, it is necessary to provide information continuously. PHBS (Clean and Healthy Lifestyle) is very influential in preventing transmission of the Covid-19 virus, especially in children. Keywords: PHBS, Covid-19